The changing UK paediatric consultant workforce: report from the Royal College of Paediatrics and Child Health. Issue 2 (27th October 2016) - McColgan, Martin; Winch, Rachel; Clark, Simon J; Ewing, Carol; Modi, Neena; Greenough, Anne
Abstract : Objectives: To determine if there had been changes in the size of the UK paediatric workforce and working patterns between 1999 and 2013. Design: Analysis of prospectively collected datasets. Setting: UK consultant paediatricians. Interventions: Data from the Royal College of Paediatrics and Child Health's workforce census from 1999 to 2013 and the annual surveys of new paediatric Certificate of Completion of Training (CCT) and Certificate of Equivalence of Specialist Registration (CESR) holders between 2010 and 2013. Main outcome measures: Paediatric consultant numbers, programmed activities (PAs) and resident shift working. Results: The UK paediatric consultant workforce grew from 1933 in 1999 to 3718 in 2013. Over the same time period, there was a decline in the number of consultants with a primary academic contract from 210 to 143. There was an increase in the proportion of consultants who were female (40% in 1999 to 50% in 2013, p<0.01). The median number of PAs declined from 11 in 2009 to 10 in 2013 (p<0.001) as did the median number of PAs for supporting professional activities (2.5–2.3, p<0.001). In 2013, 38% of new consultants in general paediatrics or neonatology were working resident shifts. Between 2009 and 2013, the proportion of less than full-time working consultants rose from 18% to 22%, which was more common among female consultants (35% vs 9%). Conclusion: The paediatric consultant workforce has doubled since 1999, but more are working less than full time. The decline in those with a primary academic contract is of concern.